Can N95 Respirators Be Reused after Disinfection? How Many Times? - Liao, Lei; Xiao, Wang; Zhao, Mervin; Yu, Xuanze; Wang, Haotian; Wang, Qiqi; Chu, Steven; Cui, Yi (ACS nano, 2020)
The coronavirus disease 2019 (COVID-19) pandemic has led to a major shortage of N95 respirators, which are essential for protecting healthcare professionals and the general public who may come into contact with the virus. Thus, it is essential to determine how we can reuse respirators and other personal protective equipment in these urgent times. We investigated multiple commonly used disinfection schemes on media with particle filtration efficiency of 95%. Heating was recently found to inactivate the virus in solution within 5 min at 70 °C and is among the most scalable, user-friendly methods for viral disinfection. We found that heat (≤85 °C) under various humidities (≤100% relative humidity, RH) was the most promising, nondestructive method for the preservation of filtration properties in meltblown fabrics as well as N95-grade respirators. At 85 °C, 30% RH, we were able to perform 50 cycles of heat treatment without significant changes in the filtration efficiency. At low humidity or dry conditions, temperatures up to 100 °C were not found to alter the filtration efficiency significantly within 20 cycles of treatment. Ultraviolet (UV) irradiation was a secondary choice, which was able to withstand 10 cycles of treatment and showed small degradation by 20 cycles. However, UV can potentially impact the material strength and subsequent sealing of respirators. Finally, treatments involving liquids and vapors require caution, as steam, alcohol, and household bleach all may lead to degradation of the filtration efficiency, leaving the user vulnerable to the viral aerosols.